2023
DOI: 10.1136/jim-2022-002407
|View full text |Cite
|
Sign up to set email alerts
|

Interplay between fat, muscle, bone mass, and oteophytes and risk for tophaceous gout

Abstract: Tophaceous gout is a common arthritis caused by the deposition of urate crystals and is related to limited joint function. Although there are reports that uric acid (UA) is associated with bone mineral density (BMD), little is known about the relationship between UA, osteophytes, and muscle. This cross-sectional case–control study was performed in patients with tophaceous gout. The control group included patients without gout. All subjects underwent BMD and body composition analyses. Age, sex, alcohol consumpt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 34 publications
0
1
0
Order By: Relevance
“…It stimulates osteoclast differentiation and suppresses osteoblast differentiation via ERK and ERK-dependent NF-Kb activation demonstrated in experiment, resulting in bone loss (10). In addition, it promotes myofibrillar proteolysis and muscle atrophy (17,(37)(38)(39). The result of our study can be explained by the antioxidant effect of uric acid, which reduces oxidative stress-related bone loss (5,8,14).…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…It stimulates osteoclast differentiation and suppresses osteoblast differentiation via ERK and ERK-dependent NF-Kb activation demonstrated in experiment, resulting in bone loss (10). In addition, it promotes myofibrillar proteolysis and muscle atrophy (17,(37)(38)(39). The result of our study can be explained by the antioxidant effect of uric acid, which reduces oxidative stress-related bone loss (5,8,14).…”
Section: Discussionsupporting
confidence: 51%
“…The subgroup analysis indicated that mechanical muscle force affects on bone strength; moreover it is affected by how much body mass is supported by the muscle and bone ( 16 ). In addition, the muscle-derived mechanical loading and cytokines via the endocrine and paracrine pathway stimulate bone development and maintenance ( 17 , 38 ).…”
Section: Discussionmentioning
confidence: 99%
“…Although mostly associated to aging, DISH has been also associated to metabolic disturbances such as overweight, hyperuricemia and diabetes [4], and also to the metabolic syndrome [5]. There is some evidence on the association of DISH with gout [5][6][7] and with the development of tophaceous gout [8,9]. This study intended to evaluate the prevalence of DISH in patients with gout, the presence of spinal and peripheral joint involvement, and the association of DISH with comorbid conditions associated to gout, clinical characteristics of gout severity, and concomitant calcium pyrophosphate arthritis (CPPA).…”
Section: Introductionmentioning
confidence: 99%